P420 Fungal detection by means of HCR using 2D-Covalent Organic Framework Nanosheet. (20th September 2022) - Gajjar, Devarshi; Baghel, Manoj Kumar; Thakkar, Harshil; Thakore, Sonal
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: The timely diagnosis of fungal infections is of prime importance for prescribing appropriate anti-fungal drugs. Current methods for fungal diagnosis involve culture-based methods, antibody-based detection using lateral flow assays and RT-PCR. In the present work, we devised a non-enzymatic amplification using 2D-Covalent Organic Framework (COF) nanosheet for the detection of fungal DNA. Objectives: (1) Validation of exfoliated 2D COF Nanosheet as an efficient DNA detection tool via Hybridization chain reaction (HCR) triggered fluorescent assay. (2) Sequence retrieval and probe generation of fungal sample and detection of extracted target DNA via fluorescent assay. Method: A novel COF was synthesized and characterization was done using FTIR, BET, TGA, XRD, and SEM. Probes for the detection of fungi ( Candida, Aspergillus, and Mucor ) were designed using NUPACK software. HCR was monitored for different time and probe concentrations and standardized reaction was used for the detection of fungal RNA. Results: FTIR, BET, TGA, XRD, and SEM confirmed the structure and formation of COF-nanosheet. H1, H2 probes at a concentration of 1 μ m and in presence of Target DNA (0.001 μ m -1 μ m ) showed HCR reaction at 1.5 h. Fluorescence quenching was observed when probes were mixed with both, bulk COF and COF-nanosheets but increased quenching Conclusion: Fungal detection can be done by means of HCR using the Covalent nanosheets.